2011
DOI: 10.1177/0160017611407767
|View full text |Cite
|
Sign up to set email alerts
|

Estimates of the Impact of Static and Dynamic Knowledge Spillovers on Regional Factor Productivity

Abstract: The authors develop an empirical approach to examine static and dynamic knowledge externalities in the context of a regional total factor productivity (TFP) relationship. Static externalities refer to current period scale or industry-size effects that have been labeled localization externalities or region-size effects known as agglomeration externalities. Dynamic externalities refer to the relationship between accumulated or prior period knowledge and current levels of innovation, where past learning-by-doing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 51 publications
3
33
0
Order By: Relevance
“…This is an appropriate way to deal with the problem of spatial autocorrelation, and to estimate the influence of spatial spillover effects. The panel version of the standard SDM model controls not only for spatial autocorrelation but also for individual heterogeneity across regions (see LeSage and Fischer 2012). Denoting our set of regions by i = 1, ..., N and our time periods by t = 1, ..., T, the empirical model to estimate the relationship between research collaboration and regional knowledge production is given by …”
Section: The Empirical Modelmentioning
confidence: 99%
“…This is an appropriate way to deal with the problem of spatial autocorrelation, and to estimate the influence of spatial spillover effects. The panel version of the standard SDM model controls not only for spatial autocorrelation but also for individual heterogeneity across regions (see LeSage and Fischer 2012). Denoting our set of regions by i = 1, ..., N and our time periods by t = 1, ..., T, the empirical model to estimate the relationship between research collaboration and regional knowledge production is given by …”
Section: The Empirical Modelmentioning
confidence: 99%
“…MAR knowledge externalities will have obtained the results with industrial maturity. Lesage and Fischer [29] tested the existence of knowledge externalities with variable total factor productivity. The scope of the study data was used in 15 EU countries.…”
Section: Literature Review Data and Methodologymentioning
confidence: 99%
“…Most of these studies on knowledge externalities present empirical results for European countries. Lesage and Fischer(2012), Autant-Bernard and LeSage(2011), Antonelli et al(2011), Zheng(2010, Fischer et al(2009), Frenken et al(2007, Suedekum and Blien(2005), Van Stel andNieuwenhuijsen(2004), De Lucio et al(2002) and Paci and Usai(1999) are the studies that have found mainly positive impacts of knowledge externalities in the European economies. However Neffke et al(2011) applied an empirical analysis for Sweden during 1974 -2004 and they found that as the maturity of an industry increases the impacts of Jacobs externalities may turn to negative.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Especially in recent years, numerous studies in knowledge externalities literature such as LeSage and Fischer(2012), Antonelli et al(2011), Zheng(2010 and Fischer et al(2009) used TFP as a dependent variable. In this study, regional TFP is also used as the dependent variable which reflects economic progress and growth of a region.…”
Section: Variables and Econometric Modelmentioning
confidence: 99%